2018
DOI: 10.1186/s40945-018-0044-1
|View full text |Cite
|
Sign up to set email alerts
|

The necessary conditions of engagement for the therapeutic relationship in physiotherapy: an interpretive description study

Abstract: BackgroundThe therapeutic relationship between patient and physiotherapist is a central component of patient-centred care and has been positively associated with better physiotherapy clinical outcomes. Despite its influence, we do not know what conditions enable a physiotherapist and patient to establish and maintain a therapeutic relationship. This knowledge has implications for how clinicians approach their interactions with patients and for the development of an assessment tool that accurately reflects the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
103
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(106 citation statements)
references
References 42 publications
2
103
0
1
Order By: Relevance
“…We would also include the clinician's interpersonal style and the continued relevance of the flexibility, honesty, respect, trustworthiness, confidence, warmth, interest and openness highlighted by authors such as Ackerman and Hilsenroth (2003) or Van Riper (1973) for SLTs working with individuals who stutter. Those aspects mirror, for example, the work of Miciak et al (2018), who identified four main conditions necessary for establishing a therapeutic relationship: being present, receptive, genuine and committed. According to the authors, these conditions in conjunction with applying communication skills, represent the intentions and attitudes of both the clinician and client.…”
Section: The Working Alliance In Stuttering Treatmentmentioning
confidence: 79%
See 3 more Smart Citations
“…We would also include the clinician's interpersonal style and the continued relevance of the flexibility, honesty, respect, trustworthiness, confidence, warmth, interest and openness highlighted by authors such as Ackerman and Hilsenroth (2003) or Van Riper (1973) for SLTs working with individuals who stutter. Those aspects mirror, for example, the work of Miciak et al (2018), who identified four main conditions necessary for establishing a therapeutic relationship: being present, receptive, genuine and committed. According to the authors, these conditions in conjunction with applying communication skills, represent the intentions and attitudes of both the clinician and client.…”
Section: The Working Alliance In Stuttering Treatmentmentioning
confidence: 79%
“…In the present study, although only one significant relation between bond and outcome was found, the scores on the bond subscale remained stable throughout the treatment period. It is possible that this stable, underlying bond, perhaps associated with clinician and client's characteristics such as being present, receptive, genuine and committed, in which, according to Miciak et al (2018), represent the intentions and attitudes in the clinical interaction and are needed for the physiotherapist and client to 'be' in a therapeutic relationship. To some extent, the bond may provide the foundation for mutual agreement of tasks and goals, which is in accordance with Wampold's (2015) Contextual Model.…”
Section: Importance Of the Working Alliance And Mutual Agreement Of Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Attending to the issue of engagement in the reablement context adds an interesting dimension to current understandings of this construct. In particular, it offers a new perspective to the relational dimension of engagement—the so‐called therapeutic alliance (Higgins et al, )—which stresses the continuity of relationship between patient and practitioner (Ferreira et al, ; Greenhalgh & Heath, ; Miciak, Mayan, Brown, Joyce, & Gross, ). However, reablement, at least in the United Kingdom, is typically delivered by multiple staff (Beresford et al, in press).…”
Section: Discussionmentioning
confidence: 99%